THE INFLUENCE OF PROMOTION, M-PAYMENT METHOD, AND PERCEIVED VALUE ON CUSTOMER PURCHASE DECISION IN KOPI KENANGAN MOBILE APP - Rotinsulu, Eve Abrillia Samanta; Kindangen, Paulus; Gunawan, Emilia M. (Universitas Sam Ratulangi, 2025)
: This study objective is to measure the influence of Promotion, M-Payment Method, and Perceived Value on customer Purchase Decision. For the purpose of this study, the researcher selected participants from the population of Kopi Kenangan mobile application users in Manado which are classified as Generation Z. This study use quantitative approach to analyze the data of 100 respondents as the research sample. Multiple Linear Regression Analysis is conducted using the SPSS statistics version 30. The result of hypothesis testing shows that promotion, m-payment method, and perceived value simultaneously have positive and significant influence on customer purchase decision; promotion has positive and significant influence on customer purchase decision; m-payment method has positive and significant influence on customer purchase decision; perceived value has positive and significant influence on customer purchase decision. Keyword: Promotion, M-Payment Method, Perceived Value, Purchase Decision